Retailing and the Public (RLE Retailing and Distribution). - Neal, Lawrence E. (Taylor and Francis, 2012)
In one of the first books to treat retailing as a subject of serious analysis, Retailing and the Public examines the state of one of the most important industries in the country. Retailing gives direct employment to more people than any other trade; it accounts for over half of national income. No other industry affects the public as much as retailing does. These facts stand as true today as they did in the 1930s, and this classic text, groundbreaking in its time, shines as much light on the present as it does the past. First published 1932.